Investment incentives under emission trading: an experimental study - Camacho-Cuena, Eva; Requate, Tilman; Waichman, Israel (Environmental and resource economics, 2012)
This paper presents the results of an experimental investigation on incentives to adopt advanced abatement technology under emissions trading. Our experimental design mimics an industry with small asymmetric polluting firms regulated by different schemes of tradable permits. We consider three allocation/auction policies: auctioning off (costly) permits through an ascending clock auction, grandfathering permits with re-allocation through a single-unit double auction, and grandfathering with re-allocation through an ascending clock auction. Our results confirm both dynamic and static theoretical equivalence of auctioning and grandfathering. We nevertheless find that although the market institution used to reallocate permits does not impact the dynamic efficiency from investment, it affects the static efficiency from permit trading.
Gesehen am 11.04.2018